Fractional utilisation of maximal oxygen uptake and running economy in well-trained African and Caucasian distance runners - Weston, A.; Mbambo, Z.; Myburgh, K.
The current study indicates higher fractional utilisation of VO2max and greater running economy in African distance runners.